European qualitative research: A celebration of diversity and a cautionary tale. Issue 5 (October 2016) - Cassell, Catherine
Abstract: This contribution aims to highlight the diversity in European qualitative management research as a way of celebrating its ongoing development within Europe. In recognising the strengths that emerge from this diversity in epistemological traditions and methods, attention is drawn to the concerns increasingly expressed by qualitative researchers about growing pressures of standardisation. It is argued that qualitative researchers should take every opportunity to encourage methodological diversity whilst resisting attempts at homogenising the experience and reporting of qualitative management research.